Transcriptomic analysis of male three-spot swimming crab (Portunus sanguinolentus) infected with the parasitic barnacle Diplothylacus sinensis. Issue 128 (September 2022) - Yang, Changping; Shan, Binbin; Liu, Yan; Wang, Liangming; Liu, Manting; Yao, Tuo; Sun, Dianrong
Abstract: Diplothylacus sinensis is reported as an intriguing parasitic barnacle that can negatively affect the growth, molting, reproduction in several commercially important portunid crabs. To better understand the molecular mechanisms of host-parasite interactions, we characterized the gene expression profiles from the healthy and D. sinensis infected Portunus sanguinolentus by high-through sequence method. Totally, the transcriptomic analysis generated 52, 266, 600 and 51, 629, 604 high quality reads from the infected and control groups, respectively. The clean reads were assembled to 90, 740 and 69, 314 unigenes, with the average length of 760 bp and 709 bp, respectively. The expression analysis showed that 18, 959 genes were significantly changed by the parasitism of D. sinensis, including 4769 activated genes and 14, 190 suppressed genes. The differentially expressed genes were categorized into 258 KEGG pathways and 647 GO terms. The GO analysis mapped 13 DEGs related to immune system process and 32 DEGs related to immune response, respectively, suggesting a potential alteration of transcriptional expression patterns in complement cascades of P. sanguinolentus . Additionally, 4 representative molting-related genes were down-regulated in parasitized group, indicating D. sinensis infection appeared to suppress the producing of ecdysteroid hormones. In conclusion, the present study improves our understanding on parasite-host interaction mechanisms, which focuses the function of Ecdysone receptor, Toll-like receptor and cytokine receptor of crustacean crabs infestation with rhizocephalan parasites. Highlights: Transcriptomic data of rhizocephalan-infected portunid crabs was first investigated. After Diplothylacus sinensis invasion, 4769 DEGs were up-regulated and 14, 190 DEGs were down-regulated. The DEGs were enriched in the pathways related to the nervous, endocrine and metabolism systems. The parasites presumably develop special strategy to repress genes in complement cascades of Portunus sanguinolentus.